State of the Art in Cross-Layer Design for Cognitive Radio Wireless Networks - Yanbing Liu; Qin Zhou (2009 International Symposium on Intelligent Ubiquitous Computing and Education : 15-16 May 2009, 2009)
Cognitive radio is a revolutionary technology, which can significantly improve the utilization of limited radio spectrum resources. The limited ability of conventional layered protocol architectures has motivated the introduction of cross-layer design solutions that allow optimized operation. In this paper, we extensively and exclusively present an overview and discussion of the general methodology for cross-layer design and investigate cross-layer optimization schemes and algorithms between different layers. In addition, we conclude the paper and provide highlight trends in cross-layer design and identify areas for future work.